Developing an ICT Based Media of English Learning for Buddhist Students at Kusalamitra Homeschooling - Junaidi, Junaidi; Shadikah, Arina Afiyati; Walyono, Walyono; Rispatiningsih, Dwi Maryani (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2022)
This study was conducted at one of Buddhist Homeschooling namely Kusalamitra Homeschooling. This study aimed to develop an ICT based application to learn English for Buddhist students of Kusalamitra Homeschooling. This recent study was a research and development study so it objected to develop an English learning application for the students. Subjects of this study were validators and Buddhist students. There were two techniques used to collect the data namely interview and questionnaires. The interview was used to identify students’ need in learning English. The questionnaires were used to validate the product and evaluate the product. The data collected were analyzed qualitatively and quantitatively. There were five procedures in conducting this study. Those were analyzing needs, designing product, developing product, implementing product, and evaluating product. Based on the research finding, this study showed that the media developed had very good quality and very worth to be implemented on the students. Penelitian ini dilaksanakan di salah satu Homeschooling Buddha yang bernama Homeschooling Kusalamitra. Penelitian ini bertujuan untuk mengembangkan media pembelajaran bahasa Inggris berbasis teknologi informasi dan komunikasi. Penelitian ini merupakan jenis penelitian dan pengembangan yang bertujuan untuk mengembangkan sebuah aplikasi pembelajaran bahasa Inggris bagi siswa. Terdapat dua subjek dalam penelitian ini yaitu validator dan juga siswa Buddha homeschooling itu sendiri. Terdapat dua teknik yang digunakan untuk mengumpulkan data yaitu melalui wawancara dan penyebaran angket. Data yang dikumpulkan kemudian dianalisis secara kualitatif dan kuantitatif. Terdapat lima langkah dalam melaksanakan penelitian ini yaitu menganalisis kebutuhan, mendesain produk, mengembangkan produk, mengimplementasikan produk, dan mengevaluasi produk. Hasil penelitian menunjukkan bahwa media yang dikembangkan masuk dalam kategori sangat baik dan sangat layak untuk digunakan oleh siswa.